Person-centre care for dementia patients (backend system) - Muhammad Saifullah (2019)
Dementia is a severe mental illness that reduces a person’s intellectual abilities to think and remember. It is more common for the elderly aged 65 and above to be affected by the disease. However, it has become more prevalent with younger adults suffering from young-onset dementia. With the increasing number of dementia patients, there is greater demand for healthcare facilities. In order to support the needs of the dementia patient, a group of university final year students has developed an online centralized platform system. There are four key objectives in this project. The first objective of the project is to improve the time required to transmit information from the server to the mobile application. The second objective in this project is to create web pages for the supervisor in the care-centre. The third objective is to research and ensure that security guidelines are followed. This will minimize any threat from occurring. The last objective in this project is to perform testing on the features implemented and fixing of bugs. The system is made up of four essential components: the ASP.NET MVC5 Framework, Microsoft SQL Server Database, Google Firebase, and web hosting. The website is built using the ASP.NET MVC5 Framework that performed the logical computation and retrieves data from Microsoft SQL Server Database. The website will be published to the world wide web by uploading the project to web hosting. Google Firebase will be used to notify users across different platforms. This report will cover the research, implementation and design aspects of the backend system such as Application Programming Interface (API) and security.